Generation and characterization of an endothelin‐2 iCre mouse. Issue 2 (12th February 2015) - Cacioppo, Joseph A.; Koo, Yongbum; Lin, Po‐Ching Patrick; Gal, Arnon; Ko, CheMyong
Summary A novel transgenic mouse line that expresses codon‐improved Cre recombinase (iCre) under regulation of the Endothelin‐2 gene (edn2) promoter was developed for the conditional deletion of genes in Endothelin‐2 lineage cells and for the spatial and temporal localization of Endothelin‐2 expression. Endothelin‐2 (EDN2, ET‐2, previously VIC) is a transcriptionally regulated 21 amino acid peptide implicated in vascular homeostasis, and more recently in female reproduction, gastrointestinal function, immunology, and cancer pathogenesis that acts through membrane receptors and G‐protein signaling. A cassette (edn2‐iCre) was constructed that contained iCre, a polyadenylation sequence, and a neomycin selection marker in front of the endogenous start codon of the edn2 gene in a mouse genome BAC clone. The cassette was introduced into the C57BL/6 genome by pronuclear injection, and two lines of edn2‐iCre positive mice were produced. The edn2‐iCre mice were bred with ROSA26‐lacZ and Ai9 reporter mice to visualize areas of functional iCre expression. Strong expression was seen in the periovulatory ovary, stomach and small intestine, and colon. Uniquely, we report punctate expression in the corneal epithelium, the liver, the lung, the pituitary, the uterus, and the heart. In the embryo, expression is localized in developing hair follicles and the dermis. Therefore, edn2‐iCre mice will serve as a novel line for conditional gene deletion in these tissues. genesis 53:245–256, 2015. © 2015 Wiley Periodicals, Inc.